Vig, Albanien. Grabung im spätantiken Kastell. Die Arbeiten im Frühjahr 2018 - Oettel, Andreas; Hoxha, Gëzim (e-Forschungsberichte des DAI, 2019)
The aim of the third German-Albanian excavation at the late Roman castrum of Vig was to examine its architecture and phases of occupation. The site is located in the North Albanian mountains, in the valley of the rivers Gjader and Voma. A coin of Maximinus Daia (308–313 AD) found in a lime kiln that dated to the time of the castrum’s erecting, furnishes a terminus post quem for the fortification, whose construction probably started shortly later in the early 3rd century AD. Wall foundations recorded inside the castrum in context with ceramics from the 5th and 6th centuries AD indicate that the castrum was still used at this time, but no longer for military purposes.